Usability evaluation of the educational website “understanding my diabetes” for Mexican patients with type 2 diabetes - Ortíz, Gabriela Ortíz; Vega García, Sandra; Islas Salinas, Cristina; Muñoz Torres, Abril Violeta; Velázquez López, Lubia (Frontiers in Public Health, 2024)
Background Diabetes education is an integral part of the treatment for the metabolic control of patients with diabetes. The use of the Internet as a tool for diabetes education, as well as its acceptance, is still under study. Aim To assess the usability of the educational website “I understand my diabetes” designed for patients with type 2 diabetes attending primary care clinics. Material and method A cross-sectional study was done in 110 patients with type 2 diabetes from two family medicine clinics, each of whom was assigned a user account on the educational website “Entiendo mi diabetes.” The web site assigned a user name and password to each patient. They were able to access the educational website at home. After a 15-day review period, participants were asked to evaluate usability using the Computer System Usability Questionnaire. Additionally, we developed an eight-item questionnaire usability focusing on diabetes care. Sociodemographic data, blood pressure, and anthropometric measurements were recorded. Glucose levels and lipid profiles were also measured. Results The patients with diabetes had a mean age of 52.7 years and a median of 5 years since they were diagnosed with diabetes. The website received a good usability rating from 89.1% of participants, with favorable assessments in all three dimensions: 87.3% for information, 85.5% for quality, and 88.2% for interface. Regarding usability specifically for diabetes care, 98.2% rated it as having good usability. Conclusion The website for education about the disease in patients “I understand my diabetes” had an adequate usability evaluation by patients, so they also considered it very useful for diabetes care. The diabetes care instrument had adequate usability and reliability.